Some affected variables of information needs occurrence of an information seeker: a comprehensive hypothetical model - Karunanayaka, K.G.D.A (My University, 2007)
Affected variables of information needs occurrence of an information seeker which discussed in this paper are an important research area of the user studies. This paper is drawn on literary reviews focusing, in particularly the information needs concepts, theories, and its affected variables which explored the cognitive metaphors and methods. Even though researchers reviewed a range of several existing published pieces of literature on the target topic, the main objective of this paper is to discuss the key concepts of information needs from different angles to unify the concept of information needs through a new dimension while designing a very comprehensive hypothetical model of information needs occurrences. This paper found that information needs occurrences happen through a complex process of involving the individual's insufficient knowledge structure. The complexity arose due to two kind of basic variables such as cognitive and socio variables. The problem of insufficient knowledge became apparent when a variety of void areas were identified in the current state of knowledge. These voids were identified through cognitive environment. The cognitive variables were found as a set of features which expresses the individual's knowledge identity and capacity. This paper suggests that some specific cognitive factors such as skill factors, knowledge factors and psychological statuses of the overall intellectual power which affected with the insufficient needs. In this context, different avenues of information needs occurrences were discussed in order to identify the nature of the needs and the characteristics involved with that process